Pengaruh Kualitas Pelayanan terhadap Kepuasan Konsumen Ayam Gepuk - Eka Prasetya, Muhammad Yoga; Ellyawati, Noor; Rahayu, Vitria Puri (Faculty of Teacher Training and Education, Mulawarman University, 2024)
This study aims to find out the effect of service quality on consumer satisfaction in Chicken Gepuk M Yamin Samarinda. This study is a causal associative research with a quantitative approach. The population of this study is all consumers who enjoy Ayam Gepuk M. Yamin, namely 96 customers who visit Ayam Gepuk M. This study uses non-probability sampling with a sample withdrawal method using incidental sampling. The data collection technique in this study uses the questionnaire method. The data analysis in this study uses simple linear regression analysis. The results of the validity test of the questionnaire items showed that all statement items in the customer satisfaction variable (X) showed the value of r calculated > r table so it can be said that the customer satisfaction variable questionnaire (X) was valid. The results of the hypothesis test analysis show that the value of sig < a or 0.000 < 0.050, then there can be a significant influence of service quality on customer satisfaction at Ayam Gepuk M. Yamin Samarinda City. So, it can be concluded that the quality of service has a significant influence on the level of consumer satisfaction at Ayam Gepuk M Yamin Samarinda.